N-acetyl-L-cysteine alleviated the oxidative stress-induced inflammation and necroptosis caused by excessive NiCl2 in primary spleen lymphocytes - Zhang, Xintong; Xu, Lihua; Ma, Wenxue; Shi, Bendong; Liu, Qiaohan; Song, Yinghao; Fang, Cheng; Liu, Pinnan; Qiao, Senqiu; Cai, Jingzeng; Zhang, Ziwei (Frontiers in Immunology, 2023)
Introduction Nickel (Ni) is widely used in industrial manufacturing and daily life due to its excellent physical and chemical properties. However, Ni has the potential to harm animals' immune system, and spleen is a typical immune organ. Therefore, it is crucial to understand the mechanism of NiCl2 damage to the spleen. The purpose of this study is to investigate the effects of different concentrations of NiCl2 exposure and intervening with strong antioxidants on spleen lymphocytes to better understand the damage mechanism of Ni on spleen lymphocytes. Methods In this experiment, mice spleen lymphocytes were used as the research object. We first measured the degree of oxidative stress, inflammation, and necroptosis caused by different NiCl2 concentrations. Subsequently, we added the powerful antioxidant N-acetyl-L-cysteine (NAC) and used hydrogen peroxide (H2O2) as the positive control in subsequent experiments. Results Our findings demonstrated that NiCl2 could cause spleen lymphocytes to produce a large number of reactive oxygen species (ROS), which reduced the mRNA level of antioxidant enzyme-related genes, the changes in GSH-PX, SOD, T-AOC, and MDA, the same to the mitochondrial membrane potential. ROS caused the body to produce an inflammatory response, which was manifested by tumor necrosis factor (TNF-α) in an immunofluorescence experiment, and the mRNA level of related inflammatory genes significantly increased. In the case of caspase 8 inhibition, TNF-α could cause the occurrence of necroptosis mediated by RIP1, RIP3, and MLKL. AO/EB revealed that spleen lymphocytes exposed to NiCl2 had significant necroptosis, and the mRNA and protein levels of RIP1, RIP3, and MLKL increased significantly. Moreover, the findings demonstrated that NAC acted as an antioxidant to reduce oxidative stress, inflammation, and necroptosis caused by NiCl2 exposure. Discussion Our findings showed that NiCl2 could cause oxidative stress, inflammation, and necroptosis in mice spleen lymphocytes, which could be mitigated in part by NAC. The study provides a point of reference for understanding the toxicological effect of NiCl2. The study suggests that NAC may be useful in reducing the toxicological effect of NiCl2 on the immune system. The research may contribute to the development of effective measures to prevent and mitigate the toxicological effects of NiCl2 on the immune system.